Fixação de nitrogênio por bactérias diazotróficas em cultivares de arroz irrigado - Kuss, Anelise Vicentini (2006)
Rice is a very important culture in the South of Brazil, with productivity mean of 6 t ha-1, requiring large amounts of nitrogen. The biological nitrogen fixation (BNF) has already been established for legumes and in gramineous plants, microrganisms of the genus Azospirillum, Herbaspirillum, Gluconacetobacter and Burkholderia have potential to BNF and growth-promoting substances production. The aim of this work was to evaluate the influence of inoculation with diazotrophic bactéria above the performance of rice in the field. Diazotrophic bacteria were measured and isolated of nine rice cultivars in Rio Grande do Sul State. Using the NFb medium ((Azospirillum brasilense/lipoferum), JNFb (Herbaspirillum), JMV (Burkholderia), LGI (Azospirillum amazonense) and LGI-P (Gluconacetobacter), 58 isolates were obtained. From these, 10 isolates obtained in NFb medium (I-02, I-08, I-14, I-20, I-26, I-31, I-36, I-42, I-48 e I-54) and A. brasilense and A. lipoferum were evaluated in vitro the N2-fixing ability and indolacetic acid production. All for BNF, A. brasilense and A. lipoferum showed greater values (41,08 e 46,82 μg N mL-1, respectively) in relation to all the isolates evaluated (7,20 a 12,99 μg N mL-1). For indolacetic acid production, the I-31 isolate was the greatest producer (13,47 μg mL-1). In experiment of greenhouse A. brasilense e A. lipoferum were used I-14, I-31, I-54 isolates, and the rice cultivars IRGA-417, IRGA-419 e IRGA-420. In nutritive solution, A. lipoferum and I-54 isolate associated with IRGA-420 rice were the major producers of dry mass (13,11 e 13,22 mg plant -1, respectively) and in soil the greater values were for A. brasilense (20,40 mg plant-1) and the I-31 isolate (16,00 mg planta-1). In the fields, the populations of diazotrophic bacteria were evaluated and the parameters of rice growth as lenght, fresh and dry mass, lenght and weight of roots, total N-content of aerial parts and productivity of grains. The collections were performed on the 40, 90 e 120 day after seedling (DAS). Doses of 0, 60 and 120 kg N ha-1 and inoculant with Azospirillum brasilense or I-31 isolate inoculant were used. At the 135 DAS the harvest was proceeded. The population of endophytic bactéria in the different rice-growing stages was obtained in culture medium, revealing great numbers present in the roots. Verified an increase at the yield of rice grains of 26,91% was verified when inoculated with A. brasilense and 17,78% when inoculated with I-31, both without the use of the N-fertilizer. In the reccommended dose for rice at 120 120 kg N ha -1, the yield of inoculated rice with A. brasilense increased 31,85% over uninoculated control and unfertilizer-N. The data obtained allow to conclude that there is a possibility to use endophytic diazotrophics bacteria isolated from regional cultivars evaluated in vitro as microrganisms towards inoculants, permitting the reducing of costs from N-fertilizer and the maintenance of rice productivity.